Understanding the impact of COVID-19 on quality of life using surveys and Mendelian randomization - Kexin Jiang; Hua Ji; Lihong Ma; Zhirong Zhao; Yiwen Zhao; Jiajie Feng; Zheng Tang; Ruiwu Dai (Scientific Reports)
Abstract The COVID-19 pandemic has significantly impacted the quality of life (QoL) of individuals in China, affecting both their physical and mental well-being. This study aims to comprehensively analyze the factors influencing QoL in China during the pandemic. In 2022, we collected data using a self-developed questionnaire (dataset 2) and obtained dataset 1 from the 2021 China General Social Survey (CGSS). After confirming the scale’s reliability and validity, we employed a random forest algorithm to prioritize the factors. Subsequently, Mendelian randomization analyses were conducted using data from the MRC IEU OpenGWAS data infrastructure. By comparing data from two periods with low and high infection rates, the results showed that among the various influences brought about by the prevalence of COVID-19, sleep disorders have a significant and widespread impact on the quality of life, especially for the elderly. Through the inclusion of Mendelian randomization analysis, we found that COVID-19 have a relative increase in the risk of developing insomnia by approximately 26.7% (OR = 1.267). These findings can inform the development of targeted interventions and strategies to improve overall well-being.